MANFAAT AKTIVITAS FISIK BAGI KESEHATAN MENTAL DAN KONSENTRASI BELAJAR MAHASISWA - Wildayati Yati; Sitti Fatimah Azzahra M (STKIP Subang, 2026)
Mental health and learning concentration are two main pillars of student academic success that currently face serious challenges due to academic pressure, sedentary lifestyle, and residual effects of the pandemic. This study aims to analyze the benefits of physical activity on the mental health and learning concentration of college students. The approach used was an analytical survey with a cross-sectional design involving 120 students from PJKR FIKK at Universitas Negeri Makassar selected using stratified random sampling. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ), mental health was measured using the Depression Anxiety Stress Scale-21 (DASS-21), and learning concentration was measured using the Concentration Grid Test (CGT) and a validated learning concentration scale. Data analysis used Pearson correlation test and multiple linear regression with significance level alpha = 0.05. Results showed a significant relationship between physical activity level and mental health (r = -0.587, p = 0.000) and between physical activity and learning concentration (r = 0.612, p = 0.000). Regression analysis showed that physical activity significantly predicted mental health (Beta = -0.547, p < 0.001) and learning concentration (Beta = 0.573, p < 0.001), with effective contributions of 32.4% and 35.7% respectively. It is concluded that regular physical activity provides highly significant benefits for improving mental health and learning concentration of college students, thus needing to be integrated as part of a holistic health intervention strategy in higher education.